Fast-response and highly selective fluorescent probes for biological signaling molecule NO based on N-nitrosation of electron-rich aromatic secondary amines. (February 2016) - Miao, Junfeng; Huo, Yingying; Lv, Xin; Li, Zhe; Cao, Hualiang; Shi, Heping; Shi, Yawei; Guo, Wei
Abstract: Nitric oxide (NO) is a ubiquitous biological messenger molecule, and plays the active roles in the regulation of various physiological processes. Although numerous NO fluorescent probes have also been successfully developed in the past ten years, it still remains challenging to increase the response rate for NO while having the high selectivity and sensitivity. In this work, a simple N -nitrosation reaction of the electron-rich aromatic secondary amine with NO under aerobic condition has been utilized for the first time to construct fluorescent probe for NO. The resulting probe1, containing a N -benzyl-4-hydroxyaniline moiety as reaction group and a BODIPY dye as fluorescence reporter, could detect NO with the fast fluorescence off-on response (within seconds), high sensitivity (nM level), and excellent selectivity over various reactive oxygen species (ROS) as well as dehydroascorbic acid (DHA), ascorbic acid (AA), and methylglyoxal (MGO). Even in the presence of glutathione (GSH, a high reactive biothiol for NO), the probe still works well for NO. Further, a mitochondria-targetable probe2 was exploited by introducing a targeted triphenylphosphonium cation into probe1 scaffold. It's excellent NO sensing performance as well as its ability to specifically target mitochondria and image NO there have been nicely demonstrated. With the two probes, the basal and stimulation-induced NO in RAW264.7 murine macrophages as well as the endogenous NO in endothelial cells after oxygen–glucose deprivation (OGD) have been successfully visualized. Graphical abstract: